Readers’ preference on the two translations of Kenneth Grahame’s “The wind in the willows” = Đánh giá của người đọc về hai bản dịch của tác phẩm “The wind in the willows” của Kenneth Grahame - Trịnh, Thị Quế (2020)
“The wind in the willow” by Kenneth Grahame - classic book for children was translated twice into Vietnamese. The first translation was in 2006 by Nguyen Tam and the second one was 5 years later – in 2011 by Nguyen Thi Cam Linh. The two translations of different styles prove to have their own strengths and drawbacks and attract the readers in different ways. This tends to cause people have the sense of comparison. The researcher is interested in this special case of the two translations of the classic children book and does this research to explore the preferences of the audience on these two translations, or even try to draw further conclusion about readership in translation. Based on the theoretical foundation drawn from previous studies, the researcher designs the questionnaire to distribute to the group of participants including sixth graders, ninth graders and twelfth graders. Then, it is followed up with the interviews. The collected data from the interview is presented in tables and figures for interpreting. The researcher sees that most of readers show their preference to Cam Linh’s version. The reasons why the readers decided on their preferences are various but the majority of the respondents prefers one specific translation because it is more comprehensive and has more natural style.